2013
DOI: 10.1210/jc.2013-1274
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Yogurts Fortified in Vitamin D and Calcium Reduces Serum Parathyroid Hormone and Markers of Bone Resorption: A Double-Blind Randomized Controlled Trial in Institutionalized Elderly Women

Abstract: This study in institutionalized elderly at high risk for osteoporotic fracture suggests that fortification of dairy products with vitamin D₃ and calcium provides a greater prevention of accelerated bone resorption as compared with nonfortified equivalent foods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 36 publications
4
50
2
Order By: Relevance
“…Kruger et al [44] showed that the rats fed the fortified diet had a higher peak bone mass, bone mineral content, and density of the lumbar spine that may be due to fortified milk formulations' improved calcium and phosphorus absorption and retention. Bonjour et al [45] pointed out that consumption of yogurts fortified Fig. 5 Effects of 12-week treatments with kefir, alendronate (ALN), or REBONE on a elastic modulus and b hardness in OVX rats by nanoindentation.…”
Section: Discussionmentioning
confidence: 99%
“…Kruger et al [44] showed that the rats fed the fortified diet had a higher peak bone mass, bone mineral content, and density of the lumbar spine that may be due to fortified milk formulations' improved calcium and phosphorus absorption and retention. Bonjour et al [45] pointed out that consumption of yogurts fortified Fig. 5 Effects of 12-week treatments with kefir, alendronate (ALN), or REBONE on a elastic modulus and b hardness in OVX rats by nanoindentation.…”
Section: Discussionmentioning
confidence: 99%
“…29 A trial of 60 female postmenopausal nursing-home residents in France showed that intake of vitamin D and calcium-fortified yogurt increased serum 25(OH)D levels and decreased serum PTH levels. 30 Animal studies have demonstrated that severely calcium-deficient diets result in abnormalities in calciotropic hormones and bone metabolism. In one study, 5-week-old male rabbit pups were fed severely calciumrestricted diets (0.026%) until 30 weeks of age (skeletal maturity); controls received 0.45% calcium diets; and the calcium-replenished group was fed a 0.026% calcium diet until age 15 weeks and thereafter fed a 0.45% calcium diet.…”
Section: Increased Calcium Excretionmentioning
confidence: 99%
“…Some examples are: milk and milk products, chapati flour, rice, rice flour, soy milk, fruit juices, breakfast cereals, sugar, salt, etc . The fortification vehicle must be a widely and regularly consumed staple food or a more processed, commercially available and affordable food, without seasonal variation in its consumption.The fortification vehicle must allow a nutrient premix to be added relatively easily using low-cost technology and in such a way so as to ensure an even distribution, within different batches of the product.The bioavailability of vitamin D in fortified foods, such as milk, milk powder, cheese [34], bread [35,36], yogurt [37], orange juice [30,38,39], etc ., is good [19]. The bioavailability of vitamin D from fortified foods fortified with vitamin D in oil-based and non-oily formulations is acceptable.…”
Section: Technological Feasibility Of Vitamin D Fortification Of Fmentioning
confidence: 99%
“…The bioavailability of vitamin D in fortified foods, such as milk, milk powder, cheese [34], bread [35,36], yogurt [37], orange juice [30,38,39], etc ., is good [19]. The bioavailability of vitamin D from fortified foods fortified with vitamin D in oil-based and non-oily formulations is acceptable.…”
Section: Technological Feasibility Of Vitamin D Fortification Of Fmentioning
confidence: 99%